Assessing the impact of community development projects in sustaining the livelihoods of project beneficiaries : evidence from selected projects in Lepelle-Nkumpi Municipality in Limpopo Province - Letsoalo, P. K.; Moyo, T. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
The aim of the study is to assess the impact of community development projects in sustaining the livelihoods of communities in Lepelle-Nkumpi Local Municipality in Limpopo Province. Community development projects play a significant role as a tool to improve socio- economic development of communities. These projects have been widely implemented in South Africa to promote and sustain the livelihoods of communities. Even though many projects are expected to generate income, assets, and capabilities for beneficiaries, their impact in sustaining livelihoods of communities is not clear when they are assessed. The study is based on mixed method approach with a sample of 20 participants, from five different types of projects, 4 participants from each project including project managers and beneficiaries. Interviews were used to collect primary and secondary data from the literature review and participants. The findings showed that although project beneficiaries assessed benefited in terms of income and employment, project interventions had a limited impact because they did not lead to any significant acquisition of assets by the beneficiaries. The study recommends that in order to promote and sustain the livelihood of the beneficiaries, customised training should be provided, community projects should be viewed as businesses, there should be continuous monitoring and evaluation from the investors or donors.
Journal article published in The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Capability; Development; Livelihoods; Projects; Sustainability; Lepelle-Nkumpi Municipality; Community development -- South Africa -- Limpopo; Rural development -- South Africa -- Limpopo; Sustainable development -- South Africa Limpopo; Municipal government -- South Africa -- Limpopo